A review of growth form and plant duration (life cycle) in Kalanchoe (Crassulaceae subfam. Kalanchooideae) in an evolutionary and classificatory framework - Smith, Gideon F.; Parihar, Bharti; Almeida, Ana M.r. (Phytotaxa, 2023)
Representatives of Kalanchoe (Crassulaceae subfam. Kalanchooideae) are well-known for having evolved a range of reproductive mechanisms, at least some of which have contributed to certain species and nothospecies having become weeds in places remote from their natural habitats. In addition, kalanchoes have evolved a range of different growth forms in response to a diversity of historical environmental pressures prevalent in the locations where they grow naturally. In terms of growth form, many species are herbaceous, soft- to firm-stemmed perennials that remain small to medium-sized. In some of these same species, variants that are annuals, biennials, or multi-annuals are found. A further group of species are perennial, multi-stemmed shrubs with slightly woody but rather brittle stems and branches. A small group of Malagasy species have woody stems and branches, to the extent that the plants are truly arborescent or nearly so. The distribution of growth form, with special reference to stem and branch morphology, across the four subgenera at present formally recognised in Kalanchoe is reviewed in an evolutionary and classificatory framework, and illustrated.